Para além da formação continuada: o compromisso social do psicólogo que trabalha com demandas escolares - Lopes, Janaína Aparecida Silva (2016)
Several studies on the formation and the role of the psychologist in the educational field have pointed out the urgent need for continued training of this professional. In this sense, this research aimed to identify and analyze the continuing education needs of psychologists working with school demands in the Mineiro Triangle region. Qualitative nature, the study was based on semi-structured interviews with four professionals working with such school demands in this region; the field diary was also used as a methodological resource. We have a psychologist from public education, one that works within the clinic, a psychologist who works with high school demands in a private school and one private school psychologist also attending kindergarten and elementary school. The interview script encompassed issues related to initial training, professional practice and continuing education. The interviews were audio recorded and from the transcription of these, we have chosen three axes of analysis: Initial Training, Performance in School Psychology area and Continuing Education. In the analyzes, it was necessary to address the Initial Training; because its inevitable general character, which does not always provide the future professional theoretical and practical knowledge to work in the educational field; courses and internships in the area, student engagement in relation to its formation process along the graduation are important conditions in this regard. As for the acting, it is clear that this can contribute to more emancipatory educational processes and asks both knowledge of public policy and on the marketing character of the private network. We also found the need for a critical theoretical framework that supports the practice developed, it is not always highlights the social commitment to work. Generally, only one participant makes a coherent work with the advances made by the School and Educational Psychology in recent decades. It is the quality of training that can help the psychologists faced the professional challenges - among them, the expectation of a clinical and decontextualized work of the constituent issues of the educational phenomenon and difficult to work with teachers. The shaft Continuing Education, all recognize the importance of this, although with different views; the four seek for continued training, but not all experienced in the most coherent way with a promoter education autonomy. The problem of training costs is one of the complaints of those who work in the private network. Training in areas such as educational psychology and neuropsychology can depart professional assumptions that underpin the School Psychology in its critical aspect. Only one participant cites artistic elements as relevant in this process, including staff appearance. We also highlight the need for the professional to realize the concrete reality, permeated by relations of domination, in which the poor working conditions in a class society, have favored the sale process in which, in turn, hinder the search for continuing education able to transform effectively educational practices. In addition to the continuing education, the study reveals the need for psychologists working with school demands rethink the purpose of their actions seeking to consolidate their practice in a critical theoretical framework, thus contributing to the processes of emancipation and transformation through an essential social commitment.